Histomorphometry of the circular peripapillary arterial ring of Zinn-Haller in normal eyes and eyes with secondary angle-closure glaucoma - Jonas, Jost B.; Jonas, Shefali B. (Acta ophthalmologica, 2010)
Purpose: To examine the location and size of the peripapillary arterial circle of Zinn-Haller (PACZH) and its associations with other eye measures in normal eyes and eyes with secondary angle-closure glaucoma. Methods: The study included 29 human globes enucleated because of malignant choroidal melanoma (n = 19) (control group) or because of secondary angle-closure glaucoma (n = 10). Anterior-posterior histological sections were morphometrically evaluated. Results: The PACZH was present in all eyes. The glaucoma group and the control group did not vary significantly in the distance from the PACZH to Bruch’s membrane (297 ± 67 versus 270 ± 67 μm; p = 0.29), optic disc border (281 ± 103 versus 391 ± 170 μm; p = 0.07), optic disc centre (1059 ± 191 versus 978 ± 205 μm; p = 0.30) and retrobulbar cerebrospinal fluid space (173 ± 58 versus 172 ± 81 μm; p = 0.97) nor in the minimal PACZH diameter (39 ± 18 versus 36 ± 18 μm; p = 0.74) and maximal PACZH diameter (78 ± 37 versus 65 ± 25 μm; p = 0.36). The PACZH location, measured as distance from Bruch’s membrane, disc border, disc centre and cerebrospinal fluid space, was not significantly associated with axial length (p > 0.39), horizontal globe diameter (p > 0.17) and vertical globe diameter (p > 0.22). Both diameters were statistically independent of axial length (p = 0.72 and p = 0.58, respectively), horizontal globe diameter (p = 0.60 and p = 0.41, respectively) and vertical globe diameter (p = 0.64 and p = 0.52, respectively). All parameters were statistically independent of age (p > 0.10) and gender (p > 0.10). Conclusions: The PACZH was present in all human eyes examined and did not vary significantly in location and diameter between eyes with secondary angle-closure glaucoma and nonglaucomatous eyes, nor between myopic versus hyperopic eyes.